Estudio de calidad, estabilidad acelerada y elaboración de la documentación técnica para obtener registros sanitario de comprimidos de Albendazol 200mg para niños, elaborados en la planta piloto de farmacia de la Facultad de Ciencias Químicas y de Salud - Cunalata Cabrera, Andrea P. (2012)
The present study aims to evaluate the quality and stability of the albendazole 200mg tablets for children, produced in the pilot plant of pharmacy, Faculty of Chemical Sciences and Health to obtain technical documentation for authorization.